BIOPHILIC INTEGRATION IN URBAN PUBLIC SPACE DESIGN : A CASE STUDY OF BNI URBAN FOREST PARK, BANDA ACEH - Shidqi, Aufa; Munawir, Munawir; Kurniadi, Ilham; Syawaluddin, Nabil; Hidayatullah, Hidayatullah; Meutia, Zya Dyena (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Urban public spaces play an important role in improving environmental quality and human well-being; however, studies examining the implementation of biophilic design in tropical urban parks remain limited, particularly in the context of coastal cities in Indonesia. This study addresses this gap by exploring the integration of biophilic design principles in BNI Urban Forest Park (Hutan Tibang), Banda Aceh. The objectives are to identify existing biophilic elements, evaluate their ecological and restorative functions, and formulate recommendations to strengthen biophilic integration in tropical urban public spaces. A qualitative-descriptive methodological framework was employed through literature review, analysis of park management documents, field observation, visual documentation, and theoretical assessment based on Kellert’s biophilic design framework. The results reveal that the park incorporates several key biophilic elements, including mangrove vegetation, tree canopies, visual connections with water, and natural-material walkways, which contribute to ecological quality, thermal comfort, and visitor well-being. Nevertheless, deficiencies were identified in environmental education facilities, biodiversity interpretation, accessibility, and integrated blue–green infrastructure. These findings suggest that while the park demonstrates substantial biophilic potential, further interventions are needed to enhance its ecological and social performance. Practical implications include the implementation of interpretive signage, functional zoning, small-scale bioretention systems, sustainable vegetation management, and community-based conservation programs. The study contributes to the development of biophilic design strategies for resilient and inclusive tropical urban parks.